Comparative study of two Rift Valley fever virus field strains originating from Mauritania - Chabert, Mehdi; Lacôte, Sandra; Marianneau, Philippe; Confort, Marie-Pierre; Aurine, Noémie; Pédarrieu, Aurélie; Doumbia, Baba; Ould Baba Ould Gueya, Mohamed; Habiboullah, Habiboullah; Beyatt, Ahmed Bezeid El Mamy; Lo, Modou Moustapha; Nichols, Jenna; et al. (PLOS Neglected Tropical Diseases, 2024)
Author summary Rift Valley fever is an arboviral zoonosis caused by Rift Valley fever virus (RVFV) belonging to the Phlebovirus genus. It poses a major risk for causing a public and animal health emergency and is a significant economic burden in many African countries. To date, our knowledge of the impact of RVFV genetic diversity on its virulence in mammalian hosts, replicative capacities, and transmission by mosquitoes is limited. In this study, we fully sequenced the genomes of two RVFV strains isolated in Mauritania during two distinct outbreaks (2010 and 2013) and showed that they were genetically distant. Interestingly, we showed that one of the strains (MRU25010-30) is able to replicate in vitro more efficiently than the other (MRU2687-3). Additionally, we showed that high levels of RNAemia and viral load in the liver are associated with rapid death in BALB/c mice infected with MRU25010-30, whereas mice infected by MRU2687-3 tend to die later with high viral load in the brain. In conclusion, our study confirms that RVFV strains from distinct genetic lineages have different phenotypic characteristics such as virulence and replication capacity. These data provide a strong basis for further studies aimed at identifying the viral genetic determinants responsible for the observed phenotypes.